1988
DOI: 10.1002/1097-0142(19881015)62:8<1582::aid-cncr2820620821>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Tenckhoff catheter cytology in patients with ovarian cancer

Abstract: In order to expose malignant cells to high concentrations of cytotoxic chemotherapeutic agents, drugs can be instilled directly into the peritoneal cavity of patients with ovarian carcinomas through a Tenckhoff catheter. The peritoneal dialysate removed during such therapy can be examined cytologically for the presence of carcinoma cells. The cytologic specimens from Tenckhoff catheters from 40 consecutive patients with primary ovarian (39) and tubal (1) cancer who received intraperitoneal chemotherapy have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
1
0
1
Order By: Relevance
“…However, it is likely that the cytologic findings may vary depending on the particular treatment method used. 6,12,13,28 In 1988, Geisinger et al 29 reported findings regarding Tenckhoff catheter fluid cytology in the context of patients receiving intraperitoneal chemotherapy for ovarian cancers. They found that nuclear irregularities and hyperchromasia may be prominent in benign mesothelial cells from Tenckhoff catheters exposed intraperitoneally to cytotoxic chemotherapy.…”
Section: ❚Table 3❚ Cytomorphologic Features Of Four Cases Of Epithelimentioning
confidence: 99%
“…However, it is likely that the cytologic findings may vary depending on the particular treatment method used. 6,12,13,28 In 1988, Geisinger et al 29 reported findings regarding Tenckhoff catheter fluid cytology in the context of patients receiving intraperitoneal chemotherapy for ovarian cancers. They found that nuclear irregularities and hyperchromasia may be prominent in benign mesothelial cells from Tenckhoff catheters exposed intraperitoneally to cytotoxic chemotherapy.…”
Section: ❚Table 3❚ Cytomorphologic Features Of Four Cases Of Epithelimentioning
confidence: 99%
“…Επίσης, επιδημιολογικές μελέτες στη δεκαετία 1970 έδειξαν ότι λ nun οιστραδιόλης για μεγάλη χρονική περίοδο αύξησε 4-8 φορές την πιθανότητα ανάπτυξης καρκίνων του ενδομητρίου. (113)(114)(115)(116)(117)(118)(119)(120).…”
Section: εικ 3 To γένωμα του Aevunclassified